I am the Central Park Jogger : a story of hope and possibility - Meili, Trisha (New York : Scribner, 2003)
For the first time since the attack in 1989, the Central Park Jogger reveals her identity and tells the story in her own words. Recent events reinforce the newsworthy interest of this extraordinary woman's experience.
Keywords: Meili, Trisha; Rape victims -- New York (State) -- New York -- Biography; Violent crimes -- New York (State) -- New York -- Case studies